Glacial and Postglacial History of the White Cloud Peaks-Boulder Mountains, Idaho, U.S.A. - Cotter, James; Bloomfield, James; Evenson, Edward (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTGlacial and glaciofluvial deposits are mapped and differentiated to develop new local, relative-age (RD) stratigraphies for the North Fork of the Big Lost River, Slate Creek and Pole Creek drainages in the White Cloud Peaks and Boulder Mountains, Idaho. This stratigraphic model expands the areal extent of the "Idaho glacial model". Volcanic ash samples collected from the study area are petrographically characterized and correlated, on the basis of mineralogy and glass geochemistry, to reference samples of identified Cascade Range tephras. Four distinct tephras are recognized including; Mount St. Helens-Set S (13,600-13,300 yr BP), Glacier Peak-Set B (11,250 yr BP), Mount Mazama (6600 yr BP) and Mount St. Helens-Set Ye (4350 yr BP). A core of lake sediments containing two tephra units was obtained from a site called "Pole Creek kettle". Pollen and sediment analyses indicate three intervals of late Pleistocene and Holocene climatic change. Cool and wet climatic conditions prevailed in the region shortly before and immediately following the deposition of the Glacier Peak-Set B ash (11,250 yr BP). Climatic warming occurred from approximately 10,500 to 6600 yr BP after which warm, dry conditions prevailed. Sediment accumulation in the kettle ceased by 4350 yr BP. The presence of Glacier Peak-Set B tephra in the base of the Pole Creek kettle core provides a minimum age of 11,250 yr BP for the retreat of valley glaciers from their Late Wisconsinan maximum position. A radiocarbon date of 8450 + 85 yr BP (SI-5181), and the presence of Mount Mazama ash (6600 yr BP) up-core support the Glacier Peak-Set B identification.